Analisis akulturasi budaya dan kepercayaan tradisional masyarakat Acheh menurut perspektif pemikiran Islam / Muhammad Arifin - Arifin, Muhammad (2017)
This study aimed to investigate the issues of cultural acculturation and traditional beliefs of the Acehnese society from Islamic perspective. Before the era of Islam, the people in that area embraced Hindu and Buddhist as their cultural and traditional beliefs. Consequently, the influence of the beliefs that are rooted within the Acehnese social structure is very difficult to completely avoid although Islam has been accepted and embraced by the society. The Acehnese society itself upholds culture and beliefs very highly as the two inseparable components. In the philosophy of life of the Acehnese society, the relationship between the components is embedded in a Hadith Majah, which is hukum ngen adat lagei zat ngen sifeut. The discussion in this thesis involves several important issues, namely the cultural acculturation and traditional beliefs of Acehnese society, the existence of a catalyst factor of cultural acculturation and traditional belief, and the formulation of solutions to the paradox tradition. The study on some of the culture and traditions of the chosen is because up so far is still a popular ritual practiced in Acheh. Primary data for this study was obtained from interviews, participation observation, and documentation, while secondary data was obtained from the literature, books, seminar papers, websites, theses and other related materials.The data was then analyzed qualitatively, inductively and deductively. The findings reveal that, the existence of some cultural and traditional beliefs within the Acehnese society was derived from the pre Islamic era. This condition was worsened by their life philosophy that is upheld highly, and their lack of understanding on their routine which actually contradict with theirown faith. Consequently, the practice is continuing. To solve this contradiction, the religious leaders and scholars in Aceh should educate the people that the current ritualsare not compliance with the Islamic faith.